Synthesis and characterization of aluminum poly-hexamethylenephosphinate and its flame-retardant application in epoxy resin. (December 2015) - Wang, Jingyu; Qian, Lijun; Xu, Bo; Xi, Wang; Liu, Xinxin
Abstract: A flame retardant additive, aluminum poly-hexamethylenephosphinate (APHP) with a polymeric structure was synthesized from 1, 5-hexadiene, hypophosphorous acid and aluminum ions. The molecular structure of APHP and thermal stability were characterized by solid nuclear magnetic resonance, Fourier transform infrared and thermogravimetric analysis. Then, APHP was applied into diglycidyl ether of bisphenol-A cured by 4, 4′-diamino-diphenylmethane. APHP showed flame-retardant effect on the epoxy thermosets in limited oxygen index (LOI), UL94 vertical test and cone calorimeter. The thermosets with only 4 wt.% APHP obtained an LOI value of 32.7% and reached the UL94 V-1 rating. The APHP/EP thermosets decreased the pk-HRR, THR and av-EHC values, decreased CO2 Y and enhanced the COY ratios, and also reserved more residual char comparing with neat thermoset. The less incorporation of APHP in thermosets will impose the better flame retardancy to epoxy thermosets. The flame-retardant effect of APHP was resulted by its two main pyrolyzed contents phosphorus and alkyl-phosphinic fragments. In condensed phase, the phosphorus-containing contents facilitated to the higher char yields and the formation of intumescent char layer, which led to a reduction of the released fuel and a strong barrier effect to weaken the combustion intensity. In gas phase, the PO, PO2 and alkyl-phosphinic fragments with quenching effect were released from the phosphorus-containing contents, and can decrease the heat release and weaken the combustion intensity.